The prevalence of intestinal parasites, undernutrition and their associated risk factors among school‐age children in Sekota Town, Northeast Ethiopia: A community‐based cross‐sectional study. Issue 3 (26th February 2023) - Debash, Habtu; Alemu, Megbaru; Bisetegn, Habtye
Abstract: Background and Aims: In developing countries, intestinal parasitic infections and malnutrition are among the most serious health issues affecting school‐aged children. They have synergetic consequences. This study aimed to determine the prevalence of intestinal parasites, undernutrition, and their associated risk factors among school‐age children. Methods: A community‐based cross‐sectional study was conducted from April to June 2021 among school‐age children in Sekota Town, Northeast Ethiopia. Households were selected using a systematic random sampling technique. Risk factor variables were collected using pretested questionnaires. Stool samples were collected from study participants and examined using a wet mount, formol‐ether concentration, and modified acid‐fast techniques. The height and weight of children were also measured using a meter and a standard calibrated balance, respectively. Data were analyzed using SPSS version 26.0 statistical software. Results: The overall prevalence of intestinal parasites among school‐age children was 44.3% (178/402). About seven species of intestinal parasites were identified. The predominant parasite identified was E. histolytica/dispar (11.2%), followed by H. nana (9.2%) and G. lamblia (6.7%). The well as a source of drinking water (adjusted odds ratio [AOR] = 7.93; 95% confidence interval [CI]: 4.38–14.36), habit of open‐field defecation (AOR = 7.02; 95% CI: 13.05–12.06), and being undernourished (AOR = 5.67; 95% CI: 2.98–10.79) were independent predictors of intestinal parasitic infections. On the other hand, the overall prevalence of undernutrition was 46.3%. Undernutrition was significantly more likely in children with a dietary diversity score (DDS) of 3 (AOR = 3.73, 95% CI: 2.37–5.88), meal frequency of no more than three times per day (AOR = 2.00, 95% CI: 1.71–2.98), intestinal parasite infection (AOR = 5.25, 95% CI: 3.24–8.52), and no access to school‐based feeding (AOR = 3.52, 95% CI: 2.17–7.96). Conclusion: The prevalence of intestinal parasitic infections and undernutrition was high among school‐age children in Sekota Town. The results imply the need for strengthening integrated strategies for the reduction of intestinal parasitic infections and undernutrition.